Pembangunan Daerah Di Pulau Sumba: Masalah Dan Tantangan - Muana Nanga (Universitas Kristen Wira Wacana Sumba, 2012)
The low quality fo human resources is one of issues faced by almost all the regions in indonesia, including all regencies in sumba. Sumba is one of the islands in Province of East Nusa Tenggara (NTT) and has 4 regencies, that is, Sumba Barat Daya, Sumba Barat, Sumba Tengah and Sumba Timur. These four rengencies in terms of human resources are relatively still left behind comparing to others regencies in Province of East Nusa Tenggara. One of the indicators used to assess the quality of human resources in one country or regency is the index of human development (IPM). The low-quality of human resources is one of the main issues and challenges in regional development in sumba. Moreover, the leakage of economic resource that flow to outside sumba and also the slow of economic transformation is also another issue faced by these 4 regencies in sumba.